E-Servqual Effect on E-Customer Satisfaction Batik Industry HadipriyantoBanyumas - Adriza, Adriza (International Journal of Psychosocial Rehabilitation, 2020)
Objective to evaluate the effect of E-ServQual to E-Satisfaction of customers which is one important factor in the sustainability of batik product marketing, especially on product sales Hadipriyanto Batik Banyumas. E-ServQual is one important factor in building E-Satisfaction of customers in buying or selling by using the facilities or e-commerce website that sells products such as batik BanyumasHadipriyanto via Facebook, Tokopedia, bukalapak. The method used is descriptive and verification. Sampling techniques using non-probability sampling (purposive sampling). Research data collection uses questionnaire consumer reports as many as 200 samples from a population of 13,400. Data were analyzed using simple linear regression analysis. Secondary data were taken from the literature and sources relevant to the research. These results indicate that E-ServQual made by the company through the website or e-commerce such as Tokopedia, bukalapak, and Facebook has been good, while E satisfaction perceived by the customer is also in both categories. E- ServQual has a significant effect on E- customer Satisfaction by 63.6%.